Coordination Strategy for Achieving Community Social Infrastructure Development Goals in Bhola, Bangladesh - Rahman, Abdur (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This paper aims at identifying the Prospects for Sustainability in Community Social Infrastructure Development having regard to Coordination Mechanisms and Stakeholders: A Case of Bhola Bangladesh. Employing a qualitative research approach, the paper seeks to establish the issues, approaches, and achievements towards owning coordination in rural setting. Interviews, focus group discussions and document review adopting both open ended questionnaires and interviews were conducted with 20 purposively selected participants drawn from different fields similar to previous study. Therefore, this study established that though there is improvement in coordination at the Bhola level, problems like resource constrains, lack of technical know-how and communication barriers are still some of the issues that hinder the functioning of agencies there. Improvement in the coordination measures entailed the maintenance of an open forum, trust amongst the stakeholders, and the adoption of the structure that captured the needs of the locals. Moreover, it was also found that for infrastructure projects to have sustainable outcomes, the community has to be involved actively in the projects. This paper adds to the studies on multi-stakeholder partnership in community advancement and offers ideas concerning the issues of advancing rural, Ashley positioned, limited asset areas. The study therefore can contribute to enhancing the coordination strategies in other contexts with the inference that equal blend of formal and informal coordination mechanism coupled with active community participation plays critical role to enhance the development of infrastructure projects.